Analisis Kualitas dan Status Mutu Air Daerah Irigasi Rawa Kakap Komplek Kabupaten Kubu Raya - Muji Listyo Widodo; Hezliana Syahwanti; Sondang Sylvia Manurung (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2022)
Daerah Irigasi Rawa (DIR) of Kakap Komplek has a potential land area of 10,725.43 Ha and a functional land area of 2,367.2 Ha. DIR Kakap Komplek is divided into 3 regions, namely Daerah Rawa (DR) Kapuas Kecil 1, DR Kapuas Kecil 2, and DR Kapuas Kecil 3. To make the DIR Kakap Komplek area a rice barn for Kubu Raya Regency, an irrigation system with sufficient water discharge is needed. and suitable irrigation water quality. Good irrigation water quality will increase plant growth and increase production yields. The problem that arises is how the suitability of the quality and status of water quality in DIR Kakap Komplek, Kubu Raya Regency based on Government Regulation of the Republic of Indonesia No. 22 of 2021. The purpose of this study was to determine whether the irrigation water quality of DIR Kakap Komplek Kakap District, Kubu Raya Regency was suitable for irrigation purposes. The research method used is descriptive method with a quantitative approach. The results of the water quality test showed that the values of TDS, TSS, NO3, Faecal Coliform and DHL were below the quality standard. Meanwhile, the values of pH, BOD, DO, COD, PO4, and MBAS are above the required quality standards. So it can be said that the quality of irrigation water in DIR Kakap Komplek still does not meet the overall quality standard parameters that have been set.